Contrastive Analysis Of Aphorisms With The Concept Of Teacher In English And Uzbek Languages (Open Academia: Journal of Scholarly Research, 2025)
Aphorisms, as concise and thought-provoking expressions, serve as a reflection of a nation’s cultural, linguistic, and philosophical worldview. This paper explores the semantic structures of aphorisms in English and Uzbek, identifying similarities and differences in their meaning, usage, and cultural implications. The study also examines the role of metaphor, symbolism, and syntactic structures in shaping the meaning of aphorisms.